Let's solve the equation step by step:
-
Start with the original equation:
\( 3(x - 5) + 2x = 0 \) -
Distribute \(3\) in the equation:
\( 3x - 15 + 2x = 0 \) -
Combine like terms:
\( 3x + 2x - 15 = 0 \)
So, the first blank is filled in with \(-15\):
3x + \(-15\) + 2x = 0
- Combine \(3x\) and \(2x\):
\( 5x - 15 = 0 \)
Now, the second blank is filled with \(15\):
5x = \(15\)
-
Isolate \(x\) by adding \(15\) to both sides:
\( 5x = 15 \) -
Divide both sides by \(5\):
\( x = 3 \)
Thus, the final value for \(x\) is:
x = \(3\)
Putting it all together, the filled out statements are:
- 3x + \(-15\) + 2x = 0
- 5x = \(15\)
- x = \(3\)